2002
DOI: 10.1111/j.1524-6175.2002.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blocker Induced Gingival Overgrowth

Abstract: Gingival overgrowth occurs with phenytoin, cyclosporin, and calcium antagonists. It can be disfiguring and painful. The prevalence of gingival overgrowth with the use of calcium antagonists may be as high as 38%. The prevalence with nifedipine may be greater than with other calcium blockers. Overgrowth occurs 3.3‐times more commonly in men than in women. Plaque control is necessary. Some patients may require gingival surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
(25 reference statements)
1
22
1
2
Order By: Relevance
“…The incidence of gingival hypertrophy with nifedipine therapy has been reported to be as high as 20%, and a 2002 study reported that the prevalence with the use of calcium channel blockers might be as high as 38%. 8,9 Here, we report a case of amlodipine-induced gingival enlargement in a 70-year-old hypertensive patient taking amlodipine at a dose of 10 mg twice daily.…”
Section: Discussion:-mentioning
confidence: 99%
“…The incidence of gingival hypertrophy with nifedipine therapy has been reported to be as high as 20%, and a 2002 study reported that the prevalence with the use of calcium channel blockers might be as high as 38%. 8,9 Here, we report a case of amlodipine-induced gingival enlargement in a 70-year-old hypertensive patient taking amlodipine at a dose of 10 mg twice daily.…”
Section: Discussion:-mentioning
confidence: 99%
“…The incidence of gingival hypertrophy with nifedipine therapy has been reported to be as high as 20%, and a 2002 study reported that the prevalence with the use of calcium channel blockers might be as high as 38%. Gingival hypertrophy is 3.3 times more common in men than in women (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…В част-ности, при патологии кардиоваскулярных органов изменения в полости рта обуслов-лены результатом нарушения системного и локального кровотока. У пациентов с гипер-тонической болезнью изменения слизистой оболочки полости рта характеризуются пре-имущественно сосудистыми, пролифера-тивными и атрофическими девиациями [1].…”
Section: Study Of the Influence Of Medicinal Preparations On The Indiunclassified